2022
DOI: 10.1126/sciadv.add2574
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric multifunctionalization of alkynes via photo-irradiated organocatalysis

Abstract: Alkynes represent a family of pivotal and sustainable feedstocks for various industries such as pharmaceuticals, agrochemicals, and materials, and they are widely used as important starting materials for the production of a broad range of chemical entities. Nevertheless, efficient structural elaborations of alkynes in chemical synthesis, especially asymmetric multifunctionalization of alkynes, remain largely unexplored. It is thus imperative to develop new asymmetric synthetic approaches, making use of these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Undoubtedly, the successful asymmetric one-pot protocol would provide a previously unknown strategy for synthesizing chiral building blocks. Very recently, our group and Lu’s group have successfully constructed chiral quaternary carbon centers using this strategy ( 46 , 47 ). In contrast to the quaternary carbon centers, the chiral tertiary carbon stereocenters at the α-position of the carbonyl group are more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, the successful asymmetric one-pot protocol would provide a previously unknown strategy for synthesizing chiral building blocks. Very recently, our group and Lu’s group have successfully constructed chiral quaternary carbon centers using this strategy ( 46 , 47 ). In contrast to the quaternary carbon centers, the chiral tertiary carbon stereocenters at the α-position of the carbonyl group are more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Recently, visible-light-induced CAM reactions have been explored for the synthesis of quaternary carbon centers, demonstrating the great potential of this reaction in multicomponent synthetic strategies (Scheme 1c). [12][13][14][15][16][17] As far as we know, visible-light-induced CAM reactions have not been applied to tertiary carbon construction. The present study describes a novel CAM/transfer hydrogenation one-pot reaction of benzoquinones, alkynes, and Hantzsch ester promoted by visible light and catalyzed by Brønsted acid.…”
Section: Introductionmentioning
confidence: 99%
“…After completion, we found that both pentacyclic isoindolinone 4a and ketenimine 4a′ had formed as reaction products. Inspired by the well-known Pictet–Spengler reaction and the potential of cumulated double bonds to experience intramolecular cyclization, 4 mL of 0.1 M HCl solution was subsequently added, causing 4a′ to efficiently undergo an intramolecular cyclization reaction, forming 4a in a total yield of 60%. Encouraged by this phenomenon, we further optimized the reaction conditions, the results of which are summarized in Table (for details, see Tables S1–S4 in the Supporting Information).…”
mentioning
confidence: 99%